Development of tennis skills training based on trainer model for beginner athletes - Ilham Aksir; Wawan Sundawan Suherman; Abdul Alim; Hasmyati Hasmyati; Andi Atssam Mappanyukki (Universitas Nusantara PGRI Kediri, 2023)
Mastery of skills in tennis is very important to master for tennis players, especially beginner tennis players who need a lot of practice time to master the skills. Currently, tennis players only have a little time to practice, given the short duration of training with a coach. A training model that can improve beginners' mastery of tennis skills is needed. This study aimed to determine the success and effectiveness of the court tennis coach model developed for novice tennis players to improve their skills. The research method used in this study is research and development (R&D). The subjects in this study were divided into 2 stages, a small experimental stage of 15 athletes and a large trial stage of 40 athletes. The instrument in this study used a tennis dyer test. Based on the results of the assessment of sports equipment development materials, tennis coaches who are competent in their fields and sports test and measurement experts in the study "Development of coach-based tennis skills training for novice athletes" stated that the quality of assistive devices is categorized as "good" for use. Based on the paired sample t-test in this study, it is known that the Sig value (2-tailed) is 0.000, which means less than 0.05 or 0.000 < 0.05. Then, there is a real difference between the pre-test and post-test dyer tennis test data for beginner court tennis athletes. The developed model of court tennis coaches is effective for novice field tennis athletes.